2000
DOI: 10.1063/1.1289236
|View full text |Cite
|
Sign up to set email alerts
|

Void-containing materials with tailored Poisson’s ratio

Abstract: Assuming square, hexagonal, and random packed arrays of nonoverlapping identical parallel cylindrical voids dispersed in an aluminum matrix, we have calculated numerically the concentration dependence of the transverse Poisson's ratios. It was shown that the transverse Poisson's ratio of the hexagonal and random packed arrays approached 1 upon increasing the concentration of voids while the ratio of the square packed array along the principal continuation directions approached 0. Experimental measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…One puts them into plastics to reduce the thermal expansion; however, for good toughness one usually also adds some rubber. [1] The numerical methodology employed has already been discussed elsewhere, [2,3] see also Gusev et al [3,4] for experimental validation. In this work we have conducted direct finite element calculations with three-phase computer models containing several hundred talcum and rubber inclusions.…”
mentioning
confidence: 99%
“…One puts them into plastics to reduce the thermal expansion; however, for good toughness one usually also adds some rubber. [1] The numerical methodology employed has already been discussed elsewhere, [2,3] see also Gusev et al [3,4] for experimental validation. In this work we have conducted direct finite element calculations with three-phase computer models containing several hundred talcum and rubber inclusions.…”
mentioning
confidence: 99%
“…Developing a sophisticated understanding of the role of porosity morphology on the dielectric characteristics of materials will help modern technology better design the mesoporous low permittivity materials which will be used as interlevel dielectrics ͑ILDs͒ for the next generation of MMICs. 29 The solid surface of a porous medium is typically complex, often fractal in nature. 26 Observe that lower permittivity values are achieved at the expense of a spectrum of other properties, such as hardness, strength, thermal con-ductivity, etc.…”
Section: Summary and Final Remarksmentioning
confidence: 99%
“…However, the role of the spatial distribution of pores has rarely been considered. Goussev et al (2000) showed that the transverse Poisson's ratio of porous materials depends strongly upon the spatial arrangement of the pores. More recently, Liu et al (2016 (a) and (c)) also identified the effect of pore distribution on the elastic responses of ordered porous materials to inner pressure.…”
Section: Introductionmentioning
confidence: 99%